2022
DOI: 10.1017/jfm.2022.67
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-driven flow of the viscoelastic Oldroyd-B fluid in narrow non-uniform geometries: analytical results and comparison with simulations

Abstract: We analyse the pressure-driven flow of the Oldroyd-B fluid in slowly varying arbitrarily shaped, narrow channels and present a theoretical framework for calculating the relationship between the flow rate $q$ and pressure drop $\Delta p$ . We first identify the characteristic scales and dimensionless parameters governing the flow in the lubrication limit. Employing a perturbation expansion in powers of the Deborah number ( $De$ ), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 68 publications
5
39
1
Order By: Relevance
“…Finally, while we considered viscous Newtonian fluids, it would be of interest to understand how the rheological response of complex fluids (such as shear thinning and viscoelasticity) influences the flow rate-pressure drop relation in deformable channels. One convenient approach to accomplish this task would be to rely on reciprocal theorems, and use a combination of the present approach and the approach recently established by Boyko and Stone [27,28] for calculating the effect of complex fluid rheology on the flow rate-pressure drop relation for rigid non-uniform channels. These calculations are left for future investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, while we considered viscous Newtonian fluids, it would be of interest to understand how the rheological response of complex fluids (such as shear thinning and viscoelasticity) influences the flow rate-pressure drop relation in deformable channels. One convenient approach to accomplish this task would be to rely on reciprocal theorems, and use a combination of the present approach and the approach recently established by Boyko and Stone [27,28] for calculating the effect of complex fluid rheology on the flow rate-pressure drop relation for rigid non-uniform channels. These calculations are left for future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…flow rate or flow rate-pressure drop relation for confined viscous Newtonian and complex fluid flows, such as in rigid channels [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…( 6) important. In this situation, the relaxation of the polymer chain will be comparable to the average transit time in the conduit, giving a non-quasi steady flow profile [58]. We will not discuss this situation in this manuscript.…”
Section: Strong Conduit Deformations (β 1)mentioning
confidence: 99%
“…Analysis of unsteady pulsatile pressure-driven flow through an elliptic cylindrical microchannel with the Navier slip condition was examined by Chuchard et al [11] using the Mathieu and modified Mathieu functions. Recently analytical solutions to the pressure-driven flow of the Oldroyd-B fluid inside a variable narrow-shaped channel were obtained by Boyko and Stone [12] using the perturbation expansion method to investigate the relationship between the flow rate and pressure drop. The study found that pressure decreases for narrow contracting channels due to shear stress.…”
Section: Introductionmentioning
confidence: 99%